Empower Open Licences to Make Educational Resources More Accessible Across Institutions - Soepriyanto, Yerry; Nugroho, Rengga Prakoso (Journal of Education for Sustainability and Diversity, 2025)
This study aims to develop a comprehensive Open Educational Resources (OER) management system to enhance educational resource accessibility across institutions. Leveraging Creative Commons licensing, the system addresses key challenges such as metadata completeness, copyright, and licensing issues. By focusing on policy clarity, privacy, and trust, the proposed system ensures efficient management and interoperability of OER. A needs assessment survey revealed a strong interest among students in cross-institutional learning resources, with respondents expressing satisfaction with existing resources and a desire for additional content. The system's editorial workflow and comprehensive metadata management optimize content visibility and usability, fostering a collaborative educational environment. The developed platform, a Progressive Web App, facilitates easy access, contribution, verification, and publication of educational content, ultimately enhancing the accessibility and quality of educational resources.